QT interval, general mortality and the role of echocardiographic parameters of left ventricular hypertrophy: results from the prospective, population-based CARLA study - Medenwald, Daniel; Kluttig, Alexander; Kors, Jan A.; Nuding, Sebastian; Tiller, Daniel; Greiser, Karin Halina; Werdan, Karl; Haerting, Johannes (European journal of preventive cardiology, 2016)
Left ventricular mass; QT interval; general population; mortality